Pengaruh Perbedaan Konsentrasi Tepung Gembili Sebagai Perekat Terhadap Kualitas Fisik Dan Organoleptik Pellet Konsentrat Sapi Potong: The Effect of Different Concentration of Gembili Flour As Adhesive on The Physical dnd Organoleptic Quality of Beef Cattle Concentrate Pellets - Wati, Nani Setiyo; Rinawidiastuti, Rinawidiastuti; Iskandar, Faruq (Jurnal Riset Agribisnis dan Peternakan, 2022)
This research aimed to examine the effect of different concentrations of gembili flour as an adhesive on the physical and organoleptic quality of beef cattle concentrate pellets. The research used a completely randomized design (CRD) with 4 treatments and 5 replications. The treatments given include A = 0%, B = 3%, C = 6%, D = 9%, and E = 12%. Parameter observed were physical quality (hardness and durability) and organoleptic (color, texture and aroma). Data were analyzed using analysis of variance and continued with Duncan’s multiple range test. The results showed that the addition of different concentrations of gembili flour had no effect on the hardness value of beef cattle concentrate pellets and had a significant effect (P<0.05) on the durability value with each mean value of 95.00; 95.75; 97.75; 97.75; 98.25%. The addition of gembili flour concentration had no effect on the color and aroma of beef cattle concentrate pellets, but had a significant effect (P<0.05) on texture with a mean score of 3.87; 3.20; 3.93; 4.67; and 4.93. The conclusion of this research is that the addition of different concentrations of gembili flour shows an influence on the durability and texture of the pellets, but does not have an influence on the hardness, color and aroma of beef cattle concentrate pellets. The addition of gembili flour as an adhesive with a concentration of 3% shows the potential to produce pellets with the best results.